2020
DOI: 10.3390/su12072969
|View full text |Cite
|
Sign up to set email alerts
|

The Dark and the Light Side of the Expatriate’s Cross-Cultural Adjustment: A Novel Framework Including Perceived Organizational Support, Work Related Stress and Innovation

Abstract: The new context of the Psychology of Sustainability and Sustainable Development has reached the attention of the scientific community in recent years, due to its comprehensive approach aimed at enhancing the sustainability of interpersonal and intrapersonal talent, as well as of groups and communities. In this scenario, research on employee cross-cultural adjustment (CCA) is considered a key theme in human resource management. It is known that psychological support in the host country may alleviate distress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 80 publications
3
25
0
3
Order By: Relevance
“…This scale was included at the end of the above-mentioned stress questionnaire [20]. Recent studies using this scale have reported Cronbach's alphas ranging from 0.72 to 0.77 [35,36].…”
Section: Organizational Orientation To Employee Welfarementioning
confidence: 99%
“…This scale was included at the end of the above-mentioned stress questionnaire [20]. Recent studies using this scale have reported Cronbach's alphas ranging from 0.72 to 0.77 [35,36].…”
Section: Organizational Orientation To Employee Welfarementioning
confidence: 99%
“…Huang et al (2018) explored the role of challenge stressors as a mediator between high-performance work systems (HPWS) and employee engagement, which showed the direct linkage of both. Giorgi et al (2020), in their study on expatriate employees' cross-cultural adjustment, found the degree of adjustment to be negatively related to work-related stress.…”
Section: The Relationship Between Challenge Stressors and Identity Ormentioning
confidence: 99%
“…Even within Western societies, public institutions in cosmopolitan cities and provincial towns could rely on different sets of moral foundations to moralize public service. Exploring these differences, within and across countries, can help PSM theory to become more applicable in explaining public service beyond Western democratic societies, and shed some light on how to manage "culture wars" within the public domain in a more and more ideologically polarized society (Rosenbloom, 2010; for cross-culture adjustment in workplace, see also Giorgi et al, 2020).…”
Section: Limitation and Future Research Directionsmentioning
confidence: 99%